(untitled) (Reflection and Critique Law Magazine, 2024)
With the advent of Law 13.467/17, the notorious "Labor Reform", were introjected into the legal system a series of changes, whether in the field of material labor law or in the field of procedural law. Among these changes is paragraph 2 of art. 8º of the CLT, which establishes that "Precedents and other statements of jurisprudence issued by the Superior Labor Court and the Regional Labor Courts may not restrict legally provided rights or create obligations that are not provided for in law." The diction of the device, in a perfunctory analysis, may lead to the conclusion that the legislator intended to avoid/prevent the interpretation of the magistrates at the time of the application of law; thus, culminating in a return to exegetic positivism (judges as mere enforcers of rules). The objective of this work is to demonstrate that, despite the fear presented by the judiciary, exegetic positivism was long surpassed by the post-positivism, and legislative innovation should be analyzed based of the Theory of Law as Integrity of Ronald Dworkin; thus, avoiding only judicial discretion (Activism) at the time of law application, but not the judge’s interpretation of positive law.